Dihydrotestosterone and Free/Total Prostatic Specific Antigen Ratio in Diagnosis and Prognosis of Prostatic Disease - Lara Balasim Al-Dahy; Basil O. Mohammed; Saad Dakhil F. Daraji; Mazin M. Farhan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Both benign prostatic hyperplasia (BPH) and prostate cancer (Pca) include prostate enlargement. The second most common cancer among men worldwide is prostate cancer. It has been documented that by the time they reach their 60s, most men will experience benign prostatic hyperplasia. There is a real difficulty differentiating between benign prostatic hyperplasia and prostate cancer, the prostatic specific antigen (PSA) is not used as a reliable marker of prostate cancer. It is a specific biomarker measure specific to prostate tissues and not prostate cancer. Aims In the analysis of the gray zone of tPSA (4-10 ng/ml), add these biochemical markers and differentiate the root cause of prostate tumor in order to minimize painful and intrusive prostate biopsy. Materials and Methods: A cross-sectional and case control study. It included 110 patients ages range (45-81 years) with benign prostatic hyperplasia (n=55) and prostate cancer (n=55). Forty -five apparently healthy subjects were also included as controls. Peripheral blood samples from controls and patients were collected before obtaining a prostatic biopsy from patients. Serum samples were used for measurements of total Prostate Specific Antigen (tPSA), Free Prostate Specific Antigen (fPSA), and Dihydrotestosterone (DHT) by using ELISA technique. Result: Mean (±SD) serum tPSA and fPSA values for Pca were substantially improved compared to both BPH and control (p=0.001 for all), while mean fPSA/tPSA values for PCa were significantly decreased compared to BPH and control values (p=0.001). In PCa, the mean +SD value of the DHT ratios was significantly lower than in each BHP, and controls (P<0.001) were significantly lower in PCa than in each BHP and regulation (P<0.001). The mean DHT values for BPH were significantly higher as compared to control values (p< 0.001). Conclusion: The level of serum tPSA is 4.2 ng/ml for prostate tumor screening, while 10.1 ng/ml for PCa and BPH differentiation.